1
$\begingroup$

I have a function: $$ \psi(t) = \frac{1}{2} \ln det\left(-\frac{\Omega(t)^{-1}}{2}\right) $$ where $\Omega(t)$ is a symmetric matrix semi-definite positive of size $k$. When I want to calculate the gradient, I have three different solutions, so I would like to know what mistakes I have made, what is the correct solution (for me case(1))

To calculate the gradient $[\ln det(X)]$ where $X$ is a matrix, I used [1], where $[\nabla \ln det(X)] = X^{-1}$

Case (1): Using the fact that $det(a\Sigma) = a^k det(\Sigma)$ where $a$ is a constant and $\Sigma$ a matrix of size $k \times k$, and [1]: \begin{align} \psi(t) &= \frac{1}{2} \left[ \ln \frac{1}{(-2)^k} - \ln det(\Omega(t)) \right]\\ \nabla_t \psi(t) &= - \frac{\Omega(t)^{-1}}{2}\\ \end{align}

Case (2): Using the fact that $det(A^{-1}) = det(A)^{-1}$, $\ln det(A)^{-1} = -\ln det(A) $ and [1]: \begin{align} \psi(t) &= -\frac{1}{2} \ln det(-2\Omega(t))\\ \nabla_t \psi(t) &= \frac{\Omega(t)^{-1}}{4}\\ \end{align}

Case(3): Using the fact that $\Xi(t) = (-2\Omega(t))^{-1}$ and [1]: \begin{align} \psi(t) &= \frac{1}{2} \ln det(\Xi(t))\\ \nabla_t \psi(t) &= \frac{1}{2} \Xi(t)^{-1} = -\Omega(t) \\ \end{align}

Thanks in advance for your help

[1] How to calculate the gradient of log det matrix inverse? or How to calculate the gradient of log det matrix inverse?

$\endgroup$
  • $\begingroup$ All of your cases attempt to calculate $\frac{\partial\psi}{\partial\Omega}$ but your question (and nabla notation) suggest that you actually wanted to calculate $$\nabla_t\phi=\frac{d\psi}{dt} = -\tfrac{1}{2}{\rm Tr}\big(\Omega^{-1}\tfrac{\partial\Omega}{\partial t}\big)$$ $\endgroup$ – greg Mar 11 at 19:13
1
$\begingroup$

Another way to solve this is by a change of variables.

You already know that for symmetric matrices

$$d \operatorname{logdet}(X) = X^{-1} : dX$$

Let $$ U = -\frac{1}{2}\Omega^{-1}; \quad U^{-1}=-2\Omega$$

then $$ dU = \frac{1}{2}{\Omega^{-1} d\Omega \Omega^{-1}} $$

We have that

$$ \eqalign{ \phi &= \frac{1}{2} \operatorname{logdet}U \\ d\phi &= \frac{1}{2}U^{-1} : dU \\ &=-\Omega : \frac{1}{2}\Omega^{-1}d\Omega\Omega^{-1} \\ &=-\frac{1}{2}\Omega^{-1} : d\Omega }$$

Thus $$\frac{\partial \phi}{\partial \Omega}= -\frac{1}{2}\Omega^{-1}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.